2019
DOI: 10.1186/s12879-019-3829-2
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 Lebanese Society of Infectious Diseases and Clinical Microbiology Guidelines for the use of antimicrobial therapy in complicated intra-abdominal infections in the era of antimicrobial resistance

Abstract: Background The Lebanese Society of Infectious Diseases and Clinical Microbiology (LSIDCM) is involved in antimicrobial stewardship. In an attempt at guiding clinicians across Lebanon in regards to the proper use of antimicrobial agents, members of this society are in the process of preparing national guidelines for common infectious diseases, among which are the guidelines for empiric and targeted antimicrobial therapy of complicated intra-abdominal infections (cIAI). The aims of these guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 62 publications
(171 reference statements)
0
20
0
Order By: Relevance
“…Characteristics of CPGsHaddad et al107 The 2018 Lebanese Society of Infectious Diseases and Clinical Microbiology Guidelines for the use of antimicrobial therapy in complicated intra-abdominal infections in the era of antimicrobial resistance.…”
mentioning
confidence: 99%
“…Characteristics of CPGsHaddad et al107 The 2018 Lebanese Society of Infectious Diseases and Clinical Microbiology Guidelines for the use of antimicrobial therapy in complicated intra-abdominal infections in the era of antimicrobial resistance.…”
mentioning
confidence: 99%
“…Shifting the types of infections treated with tigecycline was one of the main priorities of the ASP. The empiric use of tigecycline as a mono- or combination therapy to reduce carbapenem use in non-severely ill patients with cSSTI and cIAI who were at risk for infection with MDR bacteria was supported by national and international guidelines, multicenter studies, and expert opinions [ 16 , 27 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recently updated international guidelines indicate that the optimal duration of antibiotic therapy is 3–5 days in cIAI cases where patients undergo an adequate source-control procedure [ 28 , 29 ]. The duration can be extended to 7 days depending on the presence of concomitant bacteremia, rate of fever resolution and other signs of infection, and the presence of comorbidities [ 27 , 38 ]. For other infections like acute bacterial cSSTI, the latest IDSA guidelines suggest 7 to 10 days of therapy with individualization based on clinical response and factors like comorbidities, etiology, and appropriateness of drug or dosages [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of adherence to antibiotic use guidelines has already been documented in Lebanon [28,29] The above information on antibiotic use and misuse begs for national campaigns for antibiotic stewardship including guidelines and education A 2016 study of Lebanese hospitals showed that only 7% knew what the term antimicrobial stewardship meant, although around 65% reported having some type of antibiotic control program in the hospital and only 50% had an outcome measure in place [30]. However, in recent years, The Lebanese Society of Infectious Diseases has published several articles guiding the treatment of specific diseases such as UTIs and complicated intraabdominal infections [31,32]. .Moreover, the Alliance for the Prudent Use of Antibiotics (APUA) has a Lebanese chapter that has been active especially in antibiotic stewardship education [33], braving the first steps to promoting antibiotic stewardship programs in the country; steps that other nations with a similar pattern of antibiotic use should also follow.…”
Section: Discussionmentioning
confidence: 99%